Distributive Justice in Post-GAM (A Critical Review for Aceh’s Development) - Fadri, Zainal; Sari, Nur Vita; Khuwau, Dicky (Prosperity: Journal of Society and Empowerment, 2024)
Aceh's development after the 2005 Helsinki Peace Agreement presented major challenges in terms of equal distribution of resources and development benefits. This article aims to identify problems of injustice that are still ongoing in the development context of Aceh, which was previously hit by a prolonged conflict between the Free Aceh Movement (GAM) and the Indonesian government. Using a qualitative approach, this research analyzes the main aspects of distributive justice, including resource allocation, access to education and health, community participation, and natural resource management. The findings show that despite efforts to advance development, inequality in distribution and access still occurs, especially in remote areas. Therefore, this article emphasizes the need for an inclusive and transparent approach to the development process to ensure that all levels of society in Aceh can benefit fairly and equally. Thus, distributive justice is the goal and prerequisite for achieving social stability and sustainable peace in Aceh.